2004
DOI: 10.1021/ja047637t
|View full text |Cite
|
Sign up to set email alerts
|

Designer Ligands for Beryllium

Abstract: We report the rational design of ligands that selectively bind beryllium. We selected two ligands to design Be based on binding polynulear species with a Be-O-Be motif: 2-hydroxyisophthalic acid (HIPA) and 2,3-dihydroxybenzoic acid (DHBA). All previous work has focused on BeL or BeL2 species. The HIPA and DHBA have extremely high binding constants of 17.5 and 18.4, respectively. These ligands outcompete chromotropic acid, which has one the highest binding constants for Be reported in the literature for a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 11 publications
1
29
0
1
Order By: Relevance
“…4). 30 HIPA has two sixmembered ring binding pockets with carboxylate groups on either side of the phenoxide functionality, and DHBA has one six-membered and one five-membered ring binding pocket made from the two phenol groups and the carboxylic acid. Absorbance and fluorescence changes in the aromatic ligands were used to determine the binding constants directly.…”
Section: Introductionmentioning
confidence: 99%
“…4). 30 HIPA has two sixmembered ring binding pockets with carboxylate groups on either side of the phenoxide functionality, and DHBA has one six-membered and one five-membered ring binding pocket made from the two phenol groups and the carboxylic acid. Absorbance and fluorescence changes in the aromatic ligands were used to determine the binding constants directly.…”
Section: Introductionmentioning
confidence: 99%
“…A few citrate-type aqueous complexes containing CÀO units bridging two beryllium atoms are known [10,11] and very stable complexes with Be-O-Be linkages with phenolic species acting as bridging oxygen atoms have been recently reported. [12] We report here on the synthesis of a new stable citrate complex containing beryllium and aluminum atoms with a Be-O-Al linkage similar to that of beryl and a related aluminum beryllium citrate structure with bridging phosphate units that is highly soluble (1m) in aqueous phosphate solution (0.5 m). The mixed-metal citrate complex in both cases is the single dominant species in solution with no evidence of dissociation or rearrangement to Al citrate and Be citrate species.…”
mentioning
confidence: 99%
“…The deprotonation of the ahydroxy group of citric acid is unusual but has been previously reported for Al citrate complexes. [11,14] The bridging hydroxy group has been shown to be vital for the stability of beryllium citrate type complexes [10,12] but has not been characterized by X-ray diffraction studies to date. Aluminum citrate complexes have been shown to bridge through the a-hydroxy group; however, bridging hydroxy groups or water molecules were also bound to the Al atom in all but one of these cases.…”
mentioning
confidence: 99%
“…Dimethylcitric acid (DMCA) was prepared from trimethylcitrate (Aldrich) by a previously reported method [16]. NMR data ( 1 H, 9 Be, 13 C) were obtained on Bunker 400 MHz instruments. T 1 experiments followed literature precedent [17].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the strong evidence for cluster formation in water, most aqueous research has focused on monomeric BeL or BeL 2 complexes at low pH. A recent report has shown that a Be O Be motif is highly stable and selective for Be with the bridging O coming from a phenolate [9]. Also another recent report showing a Al/Be motif (A1 O Be) utilizing CA [10].…”
Section: Introductionmentioning
confidence: 99%